Endourological management of ureteric strictures after kidney transplantation: Stenting the stent - Bach, Christian (Elsevier, 2011)
The incidence of ureteric obstruction after kidney transplantation is 3–12.4%, and the most common cause is ureteric stenosis. The standard treatment remains open surgical revision, but this is associated with significant morbidity and potential complications. By contrast, endourological approaches such as balloon dilatation of the ureter, ureterotomy or long-term ureteric stenting are minimally invasive treatment alternatives. Here we discuss the available minimally invasive treatment options to treat transplant ureteric strictures, with an emphasis on long-term stenting. Using an example patient, we describe the use of a long-term new-generation ureteric metal stent to treat a transplant ureter where a mesh wire stent had been placed 5 years previously. The mesh wire stent was heavily encrusted throughout, overgrown by urothelium and impossible to remove. Because the patient had several previous surgeries, we first considered endourological solutions. After re-canalising the ureter and mesh wire stent by a minimally invasive procedure, we inserted a Memokath® (PNN Medical, Kvistgaard, Denmark) through the embedded mesh wire stent. This illustrates a novel method for resolving the currently rare but existing problem of ureteric mesh wire stents becoming dysfunctional over time, and for treating complex transplant ureteric strictures.